RANCANG BANGUN MODEL SISTEM CONTROLLING DAN OTOMATISASI ROBOT PENGANGKUT SAMPAH DALAM RUANGAN - Siregar, Riki Ruli A.; Suyanto, Suyanto (PETIR, 2015)
Trash has been a serious problem. All this time, people is used to just throw away their garbage to garbage cans and leave the res of the process to instances that are responsible for taking care the daily waste of human’s lives. In real life, garbage problems extend to the point of health and environment issues. Garbage also affects the cleanliness of a room, in which the more household consumption the more garbage is being created. The purpose of this writing is to design a controlling system model and a garbage robot automation. The result of this design is expected to help humans to carry their garbage out of their rooms.